Association of ribosomal protein S6 kinase 1 with cellular radiosensitivity of non-small lung cancer. (3rd June 2017) - Wang, Ye; Mei, Hong; Shao, Qiang; Wang, Jian; Lin, Zhenyu
Abstract: Purpose: Ribosomal S6 kinase 1 (S6K1) plays an important role in cell proliferation, protein translation and cell survival. This study investigated the possibility of using S6K1 as a new target in the radiotherapy of non-small cell lung cancer (NSCLC) and its potential mechanism. Materials and methods: shRNA interference technology was applied to silence the expression of S6K1 in A549 and H460, and clonogenic assay was performed to measure the radiosensitizing effects. DNA repair was monitored by γH2AX foci formation. Cell cycle and apoptosis were measured by flow cytometry assays. Protein expression was analyzed by Western blotting. S6K1 and lentivirus containing programmed cell death 4 (PDCD4), a substrate of S6K1, were co-transfected into cells and radiosensitivity was also detected. Results: S6K1 knockdown significantly enhanced the radiosensitivity of NSCLC cells. The notable findings in response to this combined treatment were prolonged delay in radiation-induced DNA DSB repair, robust G2/M checkpoint arrest, increased apoptosis and upregulation of PDCD4. Moreover, PDCD4 knockdown reversed the radiosensitizing effects of S6K1 inhibition in NSCLC. Conclusions: S6K1 is a promising tumor-specific target for the enhancement of NSCLC radiosensitivity and its effects may be mediated by increased expression of PDCD4.